2023
DOI: 10.1159/000528936
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Amniotic Fluid Viral Load to Predict Adverse Outcome in Pregnancies Complicated by Congenital Cytomegalovirus Infection: A Multicenter Study

Abstract: Introduction: To report the prognostic value of Cytomegalovirus (CMV) viral load in the amniotic fluid (AF) in predicting the outcome of infected pregnancies. Methods: Multicenter retrospective study involving 11 Italian referral centers from 2012 to 2021. Inclusion criteria were fetuses with confirmed congenital CMV infection. The primary outcome was the prognostic value accuracy of CMV qPCR in AF in predicting the risk of additional anomalies detected either at follow-up ultrasound or fetal MRI. The secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Sixty-seven studies underwent full text review for assessment of eligibility and 59 of these were excluded for various reasons, as listed in Figure 1. Eight studies fulfilled inclusion criteria and were included in our meta-analysis [11,12,17,[19][20][21][22][23]. These studies were published between 2009 and 2023 and originated from Europe (six from Italy, one from France, and one from Belgium) and Asia (one from Israel).…”
Section: Resultsmentioning
confidence: 99%
“…Sixty-seven studies underwent full text review for assessment of eligibility and 59 of these were excluded for various reasons, as listed in Figure 1. Eight studies fulfilled inclusion criteria and were included in our meta-analysis [11,12,17,[19][20][21][22][23]. These studies were published between 2009 and 2023 and originated from Europe (six from Italy, one from France, and one from Belgium) and Asia (one from Israel).…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that almost all infants showing clinical signs of congenital CMV infection are born to mothers who contracted a primary CMV infection during their pregnancy, and congenital CMV infection occurs in 1% of infants globally [ 25 , 26 , 27 , 28 ]. After 20 weeks of pregnancy, an ultrasound can highlight potential indications of congenital CMV infection, but these must be confirmed using serological or PCR tests [ 29 ]. The diagnosis of congenital CMV is complex and should not rely on serological tests alone.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that there is no direct correlation between the viral load in the amniotic fluid and symptoms of prenatal CMV infection [ 29 ]. Using amniocentesis to test the viral load yields a sensitivity and specificity of 66.7% and 84.3%, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the performance of fetal neurosonography can be influenced by several factors, including fetal position, gestational age at assessment, maternal body mass index and type of CNS anomalies assessed, thus making published studies difficult to compare. Furthermore, we reported recently that high viral load in the amniotic fluid is an independent predictor of the occurrence of CMV‐related anomalies on follow‐up imaging or at birth 8,9 . In light of this, generalizing about the optimal imaging technique to assess fetuses with CMV might be difficult.…”
mentioning
confidence: 99%